A shared ontology for integrated highway planning. (August 2019) - France-Mensah, Jojo; O'Brien, William J.
Abstract: Many highway agencies have several functional groups responsible for planning for safety, maintenance and rehabilitation (M&R), mobility, and other functions. The functional nature of State Highway Agencies (SHAs) can result in a siloed approach to planning. Such efforts are further challenged by functional groups utilizing legacy systems which lack interoperability. In practice, this leads to redundant planning efforts and potential spatial-temporal conflicts in the projects proposed by the different groups over a planning period. There is a need for an integrated approach to planning supported by information systems. However, the existing literature on formalized knowledge representation fails to adequately account for the level of information needed for cross-functional planning of projects scheduled for the same network. Hence, this study presents an ontology for integrating information to support the cross-functional and spatial-temporal planning of highway projects. The Integrated Highway Planning Ontology (IHP-Onto) is a shared representation of knowledge about pavement assets, M&R planning, and inter-project coordination. Sources of the knowledge acquired included expert interviews, a review of nation-wide studies, and previously published ontologies. The implementation phase included a case study demonstration of the ontology by answering relevant competency questions via SPARQL queries. Based on the data-driven evaluation of the ontology, the precision and recall rates obtained were 97% and 92% respectively. Based on the results of the evaluation approaches, IHP-Onto was demonstrated as being sufficient to represent domain knowledge capable of supporting integrated highway planning.